Regulations Concerning the ‘Temporary Period’ in The New System Sought to be Established in Cyprus and Its Properties - Soyalp Tamçelik (Gazi Akademik Bakış)
In this research, regulations concerning the ‘temporary period’ in the new system sought to be established in Cyprus and its properties have been addressed. From this point of view, as the main purpose of this research, the regulations required during the talks taking place between the parties in Cyprus before a federal state is established and how the institutions expected to fulfill these will be structured have been observed. As could be understood from its name, temporary period reflects a certain period and is the period assumed to continue in Cyprus until the formation envisioned to be established there is achieved. Therefore, it is also possible to call this period a ‘transition period’. Actually, the most consistent for-mula that could be brought forward towards this period seems to be the formula of ‘temporary joint administration based on the principle of equality’. This formula, which is important for providing the necessary element of trust for negotiation particularly on issues of territory and constitution and also for displaying whether or not the functional properties of the federal state to be established is based upon a true foundation, appears for now as the most realistic method. On the other hand, the regulations to be made during the temporary period will come into effect with the preparation of the Federal Constitution and the Electoral Law, installing federal bureaucracy, analyzing property claims, determining economic development and protective provisions, regulations regarding territorial adjustments and through Committees, formed by the two communities, in charge of preparing the activity programme. Before a Federal Republic is established, a new state of partnership will emerge after the ‘Temporary Regulations’ enter into force. This partnership will reveal itself as a new state system organized within a framework of a federation that consists of two communities from a constitutional aspect and of two regions from a territorial aspect. Based on this fact, this research consists of two main sections. In the first section, regulations regarding the Temporary Period and other works to be conducted based on the Ghali Set of Ideas have been addressed. In the second and final section, regulations concerning the Temporary Period have been observed based on the Annan Plan.